Analisis Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan pada Perusahaan Consumer Goods Terdaftar Di Bursa Efek Indonesia Periode 2016-2018 - Hasdi Suryadi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
This study aims to test empirically the independent variables consisting of profitability, company size, company age, auditor opinion, ownership structure and leverage affect the dependent variable on timeliness of financial reporting partially and simultaneously. The data population used is all consumer goods companies listed on the Indonesia Stock Exchange for the period 2016-2018. This research uses purposive sampling method, there are 24 companies that meet the criteria with a total of 72 samples used as research data. Data analysis using logistic regression analysis. The results showed that partially profitability, company size, company age, auditor opinion, ownership structure and leverage had no effect on the timeliness of financial reporting and simultaneously profitability, company size, company age, auditor opinion, ownership structure and leverage had an effect on timeliness finance report.